Two cases of multidrug-resistant genitourinary Mycoplasma genitalium infection successfully eradicated with minocycline. (April 2019) - Glaser, Allison M; Geisler, William M; Ratliff, Amy E; Xiao, Li; Waites, Ken B; Gaisa, Michael
Mycoplasma genitalium (MG) infection is a sexually transmitted infection that causes up to 25% of nongonococcal urethritis (NGU). MG strains carrying genetic markers of antimicrobial resistance that may affect treatment outcomes are increasingly recognized as a public health concern. We present two cases of persistent MG NGU with strains carrying both macrolide and quinolone resistance-associated mutations that were eradicated successfully by an extended course of minocycline.